2016
DOI: 10.1016/j.tins.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Npas4: Linking Neuronal Activity to Memory

Abstract: Immediate early genes (IEGs) are rapidly activated after sensory and behavioral experience and are believed to be critical for converting experience into long-term memory. Neuronal PAS domain protein 4 (Npas4), a recently discovered IEG, has several characteristics that make it likely to be a particularly important molecular link between neuronal activity and memory: it is among the most rapidly induced IEGs, is expressed only in neurons, and is selectively induced by neuronal activity. By orchestrating distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(160 citation statements)
references
References 79 publications
5
154
0
1
Order By: Relevance
“…Since different IEGs have unique induction profiles in different cell-types (38, 67, 68), it is critical to characterize IEG expression profiles for brain regions of interest before beginning experiments. With IEG promoters driving reporters to visualize activated neurons, the design of the transgene may dictate how faithfully the reporter follows activity.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…Since different IEGs have unique induction profiles in different cell-types (38, 67, 68), it is critical to characterize IEG expression profiles for brain regions of interest before beginning experiments. With IEG promoters driving reporters to visualize activated neurons, the design of the transgene may dictate how faithfully the reporter follows activity.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…By regulating the number of inhibitory synapses onto excitatory cells, Npas4 is critical in limiting the amount of excitation that results from stimulation . In rodent models of decreased Npas4 expression, the resulting imbalance in cortical excitation leads to several disease‐relevant behavioral outcomes including: hyperactivity, seizures, social anxiety, contextual memory impairment and increased vulnerability to stress …”
Section: Introductionmentioning
confidence: 99%
“…While this perspective article has focused on the role of Arc in glutamatergic and DA signaling in frontal cortex as a well-characterized model for activity-dependent genetic feedback, recent studies have also provided exciting insights into the functions of other IEGs in both excitatory and inhibitory neuronal circuits (Leslie and Nedivi, 2011; Sun and Lin, 2016). Particularly, it has been reported that neuronal activity induces distinctive gene expression programs in excitatory and inhibitory neurons (Spiegel et al, 2014; Mardinly et al, 2016).…”
Section: Resultsmentioning
confidence: 99%